2020
DOI: 10.4081/aiua.2020.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive evaluation of obstruction after ureteroscopic stone removal: Role of renal resistive index assessment

Abstract: Objectives: The aim of this study is to evaluate prediction of postoperative ureteral obstruction needing ureteral stent insertion by evaluating the resistive index (RI) values and the grade of hydronephrosis. Material and Methods: A total of 66 adult patients undergoing stentless endoscopic ureteral stone treatment (URS) between January 2018 and January 2019 were included in this prospective study. Preoperative patient and stone characteristics were noted. All patients were evaluated with renal Doppler ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Urolithiasis is the communal and oldest diseases of the urinary system. Currently, ureteroscopy is one of the most common procedures among various endourological operations and is performed for a variety of indications, including fragmentation and removal of ureteroscopic stones [12][13] . In 2002, Hoskin et al determined that routine stenting of ureter is unnecessary after uncomplicated ureteroscopic removal of the distal ureteral stone, and the same observation was observed in our study [14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Urolithiasis is the communal and oldest diseases of the urinary system. Currently, ureteroscopy is one of the most common procedures among various endourological operations and is performed for a variety of indications, including fragmentation and removal of ureteroscopic stones [12][13] . In 2002, Hoskin et al determined that routine stenting of ureter is unnecessary after uncomplicated ureteroscopic removal of the distal ureteral stone, and the same observation was observed in our study [14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of the acceleration phase and flattening of the flow spectrum curve in patients with renal arterial stenosis are observed in Doppler examinations ( 10 ) . It has been already proven that reduced perfusion due to obstruction of urine outflow from the pelvicalyceal system increases the peripheral resistance in the vascular bed of the kidney, which is reflected in an increase in the resistive index (RI), while the acceleration phase remains normal ( 11 , 12 ) . Doppler exam complements the information obtained from the CEUS enhancement curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasonography is a recognized method for the assessment of kidney lesions and perfusion disorders resulting from impaired patency of the renal vessels (2)(3)(4)(10)(11)(12) . Modern ultrasonography contrast agents persist in the vessels, without interstitial diffusion and glomerular filtration.…”
Section: Fig 3 3d Reconstruction Of the Ct Image Of The Abdominal Cav...mentioning
confidence: 99%
“…Published data demonstrated that NGAL could also be used as one of the most reliable markers in the assessment of kidney injury after ischemic or nephrotoxic states among which urinary obstruction is the most common (16). Lastly, Doppler sonographic evaluation of the vascular impedance in the renal parenchyma was used be to evaluate the functional or structural changes induced by acute and chronic obstructive renal diseases (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…It was used as an early, sensitive biomarker for (14)(15)(16). Lastly, by providing information about the changes in microvascular blood flow, renal parenchymal doppler sonographic evaluation of the vascular impedance renal resistivity index (RRI) may be helpful in the asssessment of the functional or structural changes caused by acute and chronic obstructive renal diseases (17)(18)(19). We aimed to evaluate the time dependant functional and morphological recovery of obstructed kidneys after JJ stenting in cases with impacted ureteral stones.…”
Section: Introductionmentioning
confidence: 99%